Vitamin D Deficiency in Children with Tuberculosis: A Cross Sectional Study - Sidra Tul Mun Tha, Saima Rasheed, Ayesha Mukhtar, Madiha Rasheed, Sehrish Naz, Muhammad Faisal Javaid (Pakistan Journal of Medical & Health Sciences, 2022)
The purpose of this study was to determine how common vitamin D insufficiency is among TB patients between the ages of 2 and 12. Specifically, a descriptive and cross-sectional research strategy was used for this investigation. The research was conducted in the Faisalabad, Pakistan location of the DHQ Hospital’s Pediatric Medicine Division. Material and Methods: In this study, total 93 patients presented to the out-patient department of Pediatrics Medicine, DHQ Hospital, Faisalabad were selected from: December, 2021 to May, 2022 and informed written consent was taken. Blood sample 3 ml of each patient was sent vitamin D levels for presence or absence of vitamin D deficiency. Results: Among the 93 cases, 44.09% (n=41) were between 2-6 years of age whereas 55.91%(n=52) were between 7-12 years of age, mean+sd was calculated as 7.14+2.22 years, 54.84%(n=51) were male whereas 45.16%(n=42) were females. Frequency of Vitamin D deficiency among children suffering tuberculosis age 2-12 years shows that 49.46% (n=46) had vitamin D deficiency. Conclusion: We concluded that the frequency of vitamin D deficiency is higher among children suffering with tuberculosis age 2-12 years; however, further multicenter studies are required to validate our results. Keywords: Children, tuberculosis, vitamin D deficiency, TB,